Dimetallic Palladium‐NHC Complexes: Synthesis, Characterization, and Catalytic Application for Direct C−H Arylation Reaction of Heteroaromatics with Aryl Chlorides. Issue 3 (17th December 2019) - Lee, Jhen‐Yi; Ghosh, Debalina; Kuo, Ya‐Ting; Lee, Hon Man
Abstract: A series of dimetallic palladium(II)‐NHC complexes comprised of 1, 4‐naphthalenyl or 9, 10‐anthracenyl spacer sandwiched between two imidazole rings was successfully synthesized. These complexes were characterized by 1 H and 13 C{ 1 H} NMR spectroscopy and elemental analysis. The structures of two dimetallic palladium complexes and a related mononuclear palladium complex to be used for comparative studies were further characterized by X‐ray diffraction. The dimetallic palladium complex with the 9, 10‐anthracenyl linker was very efficient in catalyzing direct C−H arylation reactions of heteroaromatic compounds (imidazoles, imidazo[1, 2‐ a ]pyridine, and thioazole) with a broad range of aryl chlorides, employing a mild monopalladium loading of 1.5 mol%. It allows for the effective use of aryl chlorides to prepare arylated heterocycles, previously only accessible with the more reactive bromide counterparts. Importantly, the catalytic activity of the dimetallic precatalyst was found to be higher than that of an analogous mononuclear complex. Abstract :